Surgical Stress after Open and Transumbilical Laparoscopic-Assisted Appendectomy in Children - Impellizzeri, Pietro; Simona, Angela; Grasso, Maria; Antonuccio, Pietro; Crisafi, Caterina; Scalfari, Gianfranco; Arena, Francesco; Salpietro, Carmelo; Lima, Mario; Romeo, Carmelo (European Journal of Pediatric Surgery, 2014)
Introduction The transumbilical laparoscopic-assisted appendectomy (TULAA) effects on the surgical stress response in children have not been studied. Our aim is to investigate the stress response in TULAA.Methods A total of 35 children underwent the appendectomy by open approach (OA) or TULAA approach. Interleukins (ILs)-6, -18, and -10 were measured before (T0), at the beginning (T1a), and at the end of surgery (T1b) and 24 hours after (T2).Results An increase in IL-6 levels at T1b and T2 and in IL-18 at T2 was observed after OA. A significant increase of both IL-6 and IL-18 were observed at T2 but values were less compared with OA (11.6 ± 4.4 vs. 31.9 ± 8.9 pg/mL for IL-6, p = 0.0006; 145.6 vs. 174.9 pg/mL for IL-18, p = NS).Conclusions A significant reduction in the postoperative cytokines in TULAA group suggests that this approach causes less surgical trauma in children.
Keywords: surgical stress; cytokines; transumbilical laparoscopic-assisted appendectomy; appendectomy